DINAMIKA KEKUASAAN DI ARAS LOKAL (Studi Kasus Kegagalan Pemilihan Kepala Desa Tanjung Kecamatan Koto Kampar Hulu Kabupaten Kampar - Nursanti Anggraini; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
local elite feud ninik mamak along with the young scholars and inteiektual inTanjung City District Kampar Hulu, have awakened the two camps had a falling out inthe democratic process at the village level.Each village chief election Tanking KotoKampar District of Hulu, persists two opposing camps in mengalukan sating theirchosen candidate.The occurrence of two different groups in carrying elections VillageHead Cape Town Kampar District of Hutu, originated from disagreements betweentraditional leaders and religious leaders with educated young leaders, where the mamakninik keiompok who never received ideas or renewal brought by the intellectual ingeneral they are educated.The location of this research is in the village of Tanjung District of Hulu KotoKampar Kampar district in Riau province.Type of this research is descriptive researchmethod used in this research is a qualitative method.The results showed that the dynamics of power thatled to the failure of electionsin the village Village Head Tanking Koto Kampar District of Hulu period 2014-2020.Failure in Tanjung village chief election Koto Kampar District of Hulu period2014 s / d in 2020, due to non-fulfillment of the absolute requirement that candidateswho advanced at least 3 (three) persons under Regulation Kampar District No. 4 of2007 on Procedures for Nominations, Selection, Implementation, Dismissal of villagechief andThe Village .. This condition causes the failure of election head of the villageof Tanjung Keeamatan Koto Kampar Hulu period of 2014, s / d in 2020.Factors that influence the dynamics of power in the election of village chief in thevillage of Tanjung District of Koto Kampar Hulu period 2014-2020 is;emergencewarring factions Local Elites in Intervention in Tanjung village chief Koto KamparDistrict of Hulu in the elections of Administrative Barriers Tanjung Koto KamparDistrict of Hulu period 2014-20.The existence of the special requirements of NinikMamak against each candidate Head of Tanjung KecamatanKoto Kampar Hulu period2014-2020.Keywords: Local Politics, Local Eliteand Power.